Діяльність державних архівів України із розширення документної бази дослідження Голодомору 1932–1933 рр - Удод, О. (Архіви України, 2008)
The article is focused on the impact respecting search of new archival sources related to the history of the Famine; their control and movement with a view of formation of the national memory, improvement of evidence basis of the Famine as genocide against Ukrainian people. The article includes the description of various archivists’ activities with regard to the Famine; classification of archival documents; analysis of the vital statistics record books as historical sources of the Famine.